Clínica fonoaudiológica: uma discussão sobre a terapêutica dos desvios de linguagem - Faim, Mônica Girotto Toledo de Castro (2002)
The purpose of this study is to discuss the therapeutic of speech deviation or disturbance through a reflexion which relates the shown phenomenon understanding to a proposal of a speech therapy intervention. 8ased on the fact that, the clinical phenomenon "reading" depends on the theoretical position adopted, an analysis of the three mainly sources which have guided some proposals was held. They are: Piaget's Genetic Epistemology, Formal Linguistics and "Interacionismo". The first and second analyses show problem. Thus, they do not let us touch the questions linked to the subject by the speech, in a subjective processo On the other hand, therapeutic proposals guided by the Interacionismo bring In order to understand why it is not possible to establish a more effective I "saying", I use the principies which determine the clinic structural.functioning !a d its components. This knowledge leads us to conclude that the speech therapy for speech deviation or disturbance can not be close to a model of clinical structure prompted by the medical science, since the speech problems may be touched only when they are treated by a clinical structure turned to symbolic matters. To conclude, I link the improvement of therapeutic performance to a production of knowledge which leads to the principies of co-variance and co¬ articulation of structural elements of asubjective clinic, working towards the speech pathology. Finally, I point to the need of having ali the effçrts concentrated on building an ethical speech therapy project.